On the interplay of borderline personality features, childhood trauma severity, attachment types, and social support - Schulze, Anna; Cloos, Leonie; Zdravkovic, Monika; Lis, Stefanie; Krause-Utz, Annegret (Borderline Personality Disorder and Emotion Dysregulation, 2022)
Adverse childhood experiences (ACE) have consistently been associated with borderline personality disorder (BPD). Still, it is not yet entirely understood if and how different types of ACE (emotional, physical, sexual abuse, neglect) relate to different BPD subdomains (affective instability, identity disturbance, negative relationships, self-harm). Insecure attachment and lower perceived social support are associated with both ACE and BPD and may therefore contribute to their relationship. No study so far integrated all these variables in one model, while accounting for their mutual influence on each other. We investigated the interplay of BPD subdomains, ACE, attachment, and perceived social support using a graph-theoretical approach.
Gesehen am 30.01.2023